Blossom-End Rot in Bell Pepper: Causes and Prevention - George J. Hochmuth; Robert C. Hochmuth (EDIS)
SL-284, a 5-page illustrated fact sheet by George J. Hochmuth and Robert C. Hochmuth, describes one of the most commonly observed disorders of pepper, blossom-end rot (BER) — its symptoms, calcium physiology, calcium deficiency, factors predisposing fruits to BER, and prevention. Includes references. Published by the UF Department of Soil and Water Science, April 2009.